Pengaruh Status Sosial Ekonomi Keluarga dan Teman Sebaya terhadap Prestasi Belajar Siswa Jurusan Manajemen Perkantoran SMK PGRI 2 Sidoarjo - Rieska Rahmadania Fitrianti; Ruri Nurul Aeni Wulandari (Mataram University, 2026)
This study will be examining the effect of family socio-economic status and peer group on students' learning achievement in the Office Management in SMK PGRI 2 Sidoarjo. This study utilized a quantitative method, adopting an associative research design. The study population was 221 students, but 142 respondents were chosen as samples by employing purposive sampling and Slovin formula with 5% error rate. The data collection instrument used was a structured questionnaire on a five-point Likert scale that was then analyzed through multiple linear regression, t-test, F-test, and coefficient of determination using IBM SPSS Statistics software. It is observed from the results that the family socio-economic status had a significant effect on students' learning achievement with a significance value of 0.000 and t-value of 4.656. The peer group also had a significant effect with a significance value of 0.000 and t-value of 7.154. Both the variables had a simultaneous significant effect on learning achievement with an F-value of 120.055 and significance value of 0.000. Furthermore, the coefficient of determination (R²) of 0.633 implied that the two variables contribute to 63.3% to the students' learning achievement. The findings contribute to efforts to improve vocational students’ academic achievement by providing empirical evidence for schools, teachers, and parents to strengthen family support and promote positive peer environments that encourage learning motivation and academic success.